A Critical Study of Takfeer and its Trends within the Framework of Islamic Teachings (Al Basirah, 2023)
Based on differences in religious interpretations of different texts, incidents, and events communities life together despite having various groups and divisions. One such difference results into ‘ex-communication’ which is called Takfeer (تکفیر) in Islamic terminology, in which one Muslim sect labels the other Muslim group as non-believer. Takfeer (تکفیر) is the sensitive matter which has serious effects on both the accuser as well as the accused. Today, many Muslims are accused as non-believers/disbelievers by fellow Muslims without investigating the matter. In this article the Islamic concept of Takfeer (تکفیر) will be defined along with its categories. Additionally, the conditions of takfeer (تکفیر) will be explored and their effects on accuser as well as the accused will be discussed in detail. Finally, the key issues of the concept of takfeer (تکفیر) will be aided according to the Qur’an, Sunnah, and scholars’ opinions to address the complexities of this grave matter.
Keywords: Concept of Takfeer; Excommunication; Disbeliever; Rulings; Conditions of takfeer; Necessitation of judgement